Learning Observation: The Demands of 21st Century Biology Learning in Senior High School - Anda Juanda*; Aisha Nur Maulida; Ria Yulia Gloria; Dindin Nasrudin (Universitas Syiah Kuala, 2021)
The sophistication of technology and access to information in the twenty-first century pushed education providers to transform preparing students to face a more challenging future. Effective and relevant teaching and learning strategies are needed in biology learning to meet the needs of future generations. Therefore, this study aims to observe the biology learning process in one of senior high school. A qualitative research approach with an observation method was used in this study. This research was conducted in class X SMA N 1 Tanjung, Brebes, Central Java. Data collection techniques used in this study are observation check list, questionnaires, and interviews. Observation of the biology learning process carried out focused on the lesson plan document, learning process, and interviews as well as student and teacher questionnaires on the biology learning process. The data collection process was carried out 3 times. The results obtained from this study indicate that teachers already know the demands of the curriculum and the needs of the 21st century. This can be seen from the of lesson plans made by the teacher. However, other findings from this study are, the skills of teachers in implementing the lesson plan with discovery learning methods are still not optimal. Learning activities undertaken have not yet led to the provision of student skills needed in 21st century. This research is expected to be used as a reference for improving the process of learning biology